Ethical Conduct of E-Learners and E-Teachers in Online Learning Community - Chuah, Kee Man; Vighnarajah, S.; Alvin, Ng (Allama Iqbal Open University Islamabad, 2017)
Effective teaching-learning participation in an online learning community necessitates both students and instructors to strike a balance of respect and tolerance with one another. In this perspective, participation in an online learning community does not differ much from participation in a conventional face-to-face classroom. In fact, the former requires a broader set of rules and policies to establish proper ethical conduct to avoid, if not resolve, actions that may be deemed inappropriate in an online learning community. In light of this awareness, the paper explores the actions of ethical conduct of e-Learners and eTeachers in WawasanLearn, an online learning community in Wawasan Open University. Discussion is further explored with some thoughts on current and future challenges facing ethical online education.